2021
DOI: 10.3390/cancers13051108
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomes in Patient Rectal Cancer and Different Intestine Locations: Where Does Proteasome Pool Change?

Abstract: A special problem in the surgery of rectal cancer is connected with a need for appropriate removal of intestine parts, along with the tumor, including the fragment close to the sphincter. To determine the length of fragments to remove, it is necessary to reveal areas without changes in molecule functioning, specific for tumor. The purpose of the present study was to investigate functioning the proteasomes, the main actors in protein hydrolysis, in patient rectal adenocarcinoma and different intestine locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Since the UPS is composed of a series of highly regulated proteins, there is ample opportunity to discover new targets for cancer therapy. Indeed, the expression of many different proteasome subunits are reported to be altered in multiple different cancers, including human papillary thyroid carcinoma [ 18 ], breast cancer [ 19 , 20 , 21 , 22 , 23 ], colon cancer [ 24 , 25 ], and ovarian cancer [ 26 ], among others [ 27 , 28 , 29 , 30 ]. We recently demonstrated that two members of the 19S regulatory complex, 26S proteasome non-ATPase subunits 1 (PSMD1) and 3 (PSMD3), may be potential targets for therapy in tyrosine kinase inhibitor (TKI)-resistant chronic myeloid leukemia (CML) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since the UPS is composed of a series of highly regulated proteins, there is ample opportunity to discover new targets for cancer therapy. Indeed, the expression of many different proteasome subunits are reported to be altered in multiple different cancers, including human papillary thyroid carcinoma [ 18 ], breast cancer [ 19 , 20 , 21 , 22 , 23 ], colon cancer [ 24 , 25 ], and ovarian cancer [ 26 ], among others [ 27 , 28 , 29 , 30 ]. We recently demonstrated that two members of the 19S regulatory complex, 26S proteasome non-ATPase subunits 1 (PSMD1) and 3 (PSMD3), may be potential targets for therapy in tyrosine kinase inhibitor (TKI)-resistant chronic myeloid leukemia (CML) cells.…”
Section: Introductionmentioning
confidence: 99%